2018
DOI: 10.12659/ajcr.906051
|View full text |Cite
|
Sign up to set email alerts
|

Pneumomediastinum and Pneumothorax Associated with Herpes Simplex Virus (HSV) Pneumonia

Abstract: Patient: Male, 37Final Diagnosis: HSV pneumoniaSymptoms: Cough • fever • sobMedication: —Clinical Procedure: —Specialty: Infectious DiseasesObjective:Unusual clinical courseBackground:Pneumonia is one of the most common causes of death from infectious disease in the United States (US). Although most cases of community-acquired pneumonia (CAP) are secondary to bacterial infection, up to one-third of cases are secondary to viral infection, most commonly due to rhinovirus and influenza virus. Pneumonia due to her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Pneumothorax has been reported with many infections like Influenza [ 11 ], Herpes simplex virus [ 12 ], and Pneumocystis pneumonia [ 13 ]. Although acute respiratory distress syndrome (ARDS) is the primary cause of mortality in COVID-19 infection, early diagnosis and treatment of serious complications such as pneumothorax [ 14 , 15 ], pneumomediastinum [ 16 , 17 ], or pulmonary embolism [ 18 ] also carry utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumothorax has been reported with many infections like Influenza [ 11 ], Herpes simplex virus [ 12 ], and Pneumocystis pneumonia [ 13 ]. Although acute respiratory distress syndrome (ARDS) is the primary cause of mortality in COVID-19 infection, early diagnosis and treatment of serious complications such as pneumothorax [ 14 , 15 ], pneumomediastinum [ 16 , 17 ], or pulmonary embolism [ 18 ] also carry utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous pneumomediastinum is defined as air in the mediastinum without evident causes (eg, traumatic, iatrogenic, hollow organ perforation, gas‐producing infection surgery, or any other interventions) 8 . Numerous reports 24‐56 have demonstrated that several lung infections, mainly influenza, provoke pneumomediastinum. Radiological features are different in influenza pneumonia compared with COVID‐19 and pneumomediastinum is believed to be a much less frequent complication (or never occurs) in COVID‐19 pneumonia 31,32,35,37,57 .…”
Section: Discussionmentioning
confidence: 99%
“…If an esophageal rupture is in the differential, a fluoroscopic esophagogram can be obtained, as was the case in our patient. If contrast is seen freely flowing through the esophagus without obstruction or diffusing out of the esophagus, rupture and obstruction are both much less likely [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…The gas produced internally, during a pneumomediastinum, can track from the mediastinum to the subcutaneous tissues, usually of the neck and chest. This gas may also make its way into the retropharyngeal fascia, producing a rare clinical picture of retropharyngeal emphysema (RPE) [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%